Evaluation of the VVIP Security System in Cases of Terrorism in Indonesia - Christo Manafe; Sapto Priyanto; Imam Subandi (Ridwan Institute, 2023)
Acts of terrorism targeting Very Very Important Person (VVIP) have occurred several times in Indonesia. This shows that VVIP is one of the targets of terrorist attacks. So that the evaluation of the VVIP security system is mandatory, so that VVIP do not become victims of terrorist attacks again. The human factor, namely the mistakes of VVIP security officers, became the dominant factor in the success of terrorist attacks on VVIP. Strict sanctions against security officers who violate applicable rules need to be implemented so that other security officers do not repeat them. The implementation of a strict VVIP security system SOP is a must so that no more terrorist attacks against VVIP occur. In routine activity theory, a capable guard system can prevent a person from becoming a target for crime (terrorism).